A qualitative study of women's experiences of familial ovarian cancer screening. Issue 11 (26th June 2013) - Lifford, Kate J.; Clements, Alison; Fraser, Lindsay; Lancastle, Deborah; Brain, Kate
Abstract: Objective: One risk management strategy that women at increased familial risk of ovarian cancer may use is screening. Until recently, this has been available as part of the UK Familial Ovarian Cancer Screening Study (UKFOCSS), using ultrasound scans of the ovaries and tumour marker blood tests. The present study aimed to gain an in‐depth understanding of women's experiences of participating in ovarian cancer screening. Methods: Semi‐structured interviews were conducted with 48 UKFOCSS participants. Interviews were recorded, transcribed and relevant sections analysed using a framework approach. Results: Screening provided women with reassurance which they found beneficial. A sense of privilege, as well as feeling proactive in potentially detecting ovarian cancer at an early stage was described. The wider benefit to research and the potential impact this could have on others was also important to women. Negative experiences of screening included worry about the screening tests and results, false reassurance by test results and disappointment with ineffective screening. Aspects of the screening study, such as the logistics, organisation and communication, were described as both good and problematic. When weighed up by the women, most described an overall positive experience of screening. Conclusions: Women reported both positive and negative experiences of screening. Overall, screening seemed to be an acceptable risk management strategy to most women who participated in this interview study. Improvements could be made particularly in helping women to understand the limitations of familial ovarian cancer screening in order to avoid false reassurance. Copyright © 2013 John Wiley & Sons, Ltd.